Long-term analysis of oncological outcomes after laparoscopic radical cystectomy in Europe: results from a multicentre study by the European Association of Urology (EAU) section of Uro-technology - Albisinni, Simone; Rassweiler, Jens (BJU international, 2015)
Objective To report long-term outcomes of laparoscopic radical cystectomy (LRC) in a multicentre European cohort, and explore feasibility and safety of LRC. Patients and Methods This study was coordinated by European Association of Urology (EAU)-section of Uro-technology (ESUT) with nine centres enrolling 503 patients undergoing LRC for bladder cancer prospectively between 2000 and 2013. Data were retrospectively analysed. Descriptive statistics were used to explore peri- and postoperative characteristics of th ecohort. Kaplan-Meier curves were constructed to evaluate recurrence-free survival (RFS), cancer-specific survival (CSS) and overall survival (OS). Outcomes were also stratified according to tumour stage, lymph node (LN) involvement and surgical margin status. Results Minor complications (Clavien I-II) occurred in 39% and major (IIIa-IVb) in 17%. In all, 10 (2%) postoperative deaths were recorded. The median (interquartile, IQR) LN retrieval was 14 (9-17) and positive surgical margins were detected in 29 (5.8%) patients. The median (mean, IQR) follow-up was 50 (60, 19-90), during which 134 (27%) recurrences were detected. Actuarial RFS, CSS and OS rates were 66%, 75% and 62% at 5 years and 62%, 55%, 38% at 10 years. Significant differences in RFS, CSS and OS were found according to tumour stage, LN involvement and margin status (log-rank P < 0.001). On multivariate Cox analysis, T stage and LN involvement (both P < 0.001) were significant predictors of RFS, CSS and OS. Positive margins were significant predictors of RFS (P = 0.016) and CSS (P = 0.043). Conclusions In this European LRC multicentre study, the largest to date, long-term RFS, CSS and OS rates after LRC appear comparable to those reported in current open RC series. Further randomised controlled trials are necessary to assess the global impact of LRC.